A PEDOT:PSS nanofiber structural material and a preparation method and application thereof
Patent Information
- Application Number
- CN202611188747.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-27
AI Technical Summary
本发明给出的制备方法首次提出将凝固浴诱导相分离与高速剪切流场相结合,通过微量注射将PEDOT:PSS溶液以200μL/min~1000μL/min的注射速度均匀注入转速为15000rpm~25000rpm的高速旋转的凝固浴中,在高速剪切流场中,PEDOT:PSS胶体受到强烈的拉伸和剪切作用,同时与凝固浴接触后发生盐析诱导的胶体失稳和相分离,并在剪切拉伸作用下使PEDOT链段伸展,形成独特的纳米枝状结构。这种结构显著增加了PEDOT链段的有序性和结晶度,有利于载流子的传输,XRD结果显示相较于原始PEDOT:PSS,纳米枝状凝聚体在2θ约为26°处显示出更尖锐的衍射峰,表明剪切力诱导了PEDOT链的有序排列和结晶度提升,其电导率可提升2个数量级以上,另外在凝固浴剪切过程中,亲水性的PSS倾向于向水相或凝固浴中扩散,而疏水性的PEDOT则快速凝聚,从而提高了PEDOT在凝聚体中的相对含量和纯度,进一步提升了导电性能,与此同时所形成的纳米枝状结构具有高比表面积和三维互连网络,枝状结构之间的物理搭接和纠缠增强了材料的机械强度和结构稳定性,同时提供了丰富的导电通路,使材料具有更高的导电能力和黏度,且由于过量PSS的去除,该纳米枝状PEDOT:PSS凝聚体具有显著降低的固有酸性和更高的生物相容性,特别适用于与生物组织直接接触的应用场景。
Smart Images

Figure CN122980073A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of conductive polymer technology, specifically relating to a PEDOT:PSS nanofiber structure material, its preparation method, and its application. Background Technology
[0002] Poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) is one of the most widely studied and promising conductive polymers. Its excellent water dispersibility, high conductivity, and good film-forming properties have made it a focus of attention in applications such as organic electronic devices, sensors, bioelectrodes, bioelectrical signal detection, neural interfaces, and tissue engineering.
[0003] However, to maintain the dispersion stability of PEDOT:PSS in water, an excessive amount of insulating PSS component is usually added. This causes PEDOT to tend to maintain a benzene structure and exhibit a coiled conformation, thus severely limiting its intrinsic conductivity. To improve the conductivity of PEDOT:PSS, researchers have explored various doping and post-treatment methods, such as polar solvent doping (ethylene glycol and DMSO, etc.), chemical doping (polyethylene glycol and polyols, etc.), and acid treatment. These methods mainly induce phase separation between PEDOT and PSS, promoting the assembly of PEDOT molecules into a larger conductive phase, thereby improving conductivity. However, these methods suffer from time-consuming and complex operations, as well as difficulties in removing dopant residues. More importantly, the PSS removal efficiency is limited, with some PSS remaining inside the material, thus limiting further improvements in the material's conductivity and stability in aquatic environments.
[0004] To address the aforementioned issues, Okuzaki et al. developed a wet spinning method for preparing PEDOT:PSS microfibers. This method involves extruding a continuous column of PEDOT:PSS aqueous dispersion through a spinneret and then injecting it into an acetone coagulation bath. Solvent exchange between water and acetone, dehydration, and solidification result in continuously wound one-dimensional linear PEDOT:PSS microfibers. While the structural stability of the obtained PEDOT:PSS microfibers is somewhat improved in an aqueous environment, the resulting PEDOT:PSS microfibers are one-dimensional linear materials with a uniform morphology. The diameter of these materials is typically on the micrometer scale, making it difficult to construct nano-conductive networks with high specific surface area. Furthermore, the improvement in PEDOT crystallinity is limited, resulting in a limited effect on enhancing overall conductivity. Therefore, it is difficult to simultaneously optimize conductivity and structural processability. Summary of the Invention
[0005] To address the shortcomings of the existing technology, the present invention aims to provide a PEDOT:PSS nanofiber structure material, its preparation method, and its applications. This preparation method involves injecting a PEDOT:PSS aqueous solution into a high-speed shear coagulation bath flow field. Utilizing the highly efficient and controllable high-speed shear flow field to induce the synergistic effect of phase separation and shear stretching, not only is rapid aggregation of PEDOT:PSS achieved, forming a unique nano-dendritic structure, but also PSS migration and removal are promoted, and the orderliness and crystallinity of PEDOT segments are improved, thereby enhancing the material's electrical conductivity and stability.
[0006] To address the aforementioned technical problems, this invention provides a method for preparing PEDOT:PSS nanofiber structured materials, comprising the following steps: The coagulation bath medium is subjected to high-speed shearing at a rotation speed of 15,000 rpm to 25,000 rpm to form a high-speed shear flow field. The coagulation bath medium is a saturated inorganic salt solution. PEDOT:PSS aqueous solution was injected into a high-speed shear flow field at an injection rate of 200 μL / min to 1000 μL / min for high-speed shearing. After the formation of black flocculent condensate, the injection and shearing were stopped. The condensate was washed and dried to obtain nano-dendritic PEDOT:PSS condensates. The amount of PEDOT:PSS aqueous solution added did not exceed one-tenth of the volume of the coagulation bath medium, and the solid content of the PEDOT:PSS aqueous solution was 0.5wt% to 2.0wt%.
[0007] Unlike organic coagulation baths such as acetone and isopropanol, which mainly rely on solvent exchange and dehydration to solidify the continuous liquid column of PEDOT:PSS, the saturated salt water solution used in this invention mainly reduces the electrostatic repulsion between PEDOT:PSS colloidal particles by generating charge shielding and salting out through high ionic strength, inducing their instability and phase separation, while water remains as the continuous phase.
[0008] Based on this, the preparation method presented in this invention is the first to combine coagulation bath-induced phase separation with a high-speed shear flow field. PEDOT:PSS solution is uniformly injected into a high-speed rotating coagulation bath at an injection rate of 200 μL / min to 1000 μL / min via micro-injection. During this process, saturated salt-induced aggregation and dispersion, stretching, refinement, and reassembly caused by high-speed shearing occur synergistically. In the high-speed shear flow field, the PEDOT:PSS colloid is subjected to strong stretching and shearing. Simultaneously, upon contact with the coagulation bath, salting-out-induced colloidal instability and phase separation occur. Under shear and stretching, the PEDOT segments extend, forming a unique nano-dendritic interconnected aggregate structure, rather than the continuous micron-sized filaments formed by traditional wet spinning. This structure significantly increases the order and crystallinity of the PEDOT segments, which is beneficial for carrier transport and improves conductivity.
[0009] The coagulation bath medium undergoes high-speed shearing at a stirring speed of 15,000 rpm to 25,000 rpm. This high shearing speed affects the velocity gradient, fluid shearing, and the dispersion and stretching of PEDOT:PSS agglomerates within the coagulation bath. When the speed is below 15,000 rpm, the shearing and stretching forces generated by the flow field are insufficient, causing the PEDOT:PSS aqueous solution to rapidly coagulate locally upon entering the coagulation bath, forming large, unevenly distributed flocculent or blocky agglomerates, making it difficult to obtain uniform, continuous nano-dendritic structures. When the speed is within the range of 15,000 rpm to 25,000 rpm, the interface between the coagulation bath and the PEDOT:PSS aqueous solution can be rapidly renewed. The salt-induced phase separation process can synergize well with the shearing, stretching, and dispersion processes, thereby inhibiting the formation of large agglomerates and promoting the construction of nano-dendritic structures.
[0010] A PEDOT:PSS aqueous solution was injected into a high-speed shear flow field at an injection rate of 200 μL / min to 1000 μL / min, and high-speed shearing continued. The injection rate affects the PEDOT:PSS content entering the coagulation bath per unit time and the matching relationship between phase separation, agglomeration, and shear dispersion processes. When the injection rate is below 200 μL / min, the PEDOT:PSS feed rate is low, the number of aggregated structures formed per unit time is small, and it is difficult for aggregates to continuously overlap and assemble, easily forming scattered, fragmented, or discontinuous branched fibrous products, while the production efficiency is low. When the injection rate is in the range of 200 μL / min to 1000 μL / min, the continuous feeding process of PEDOT:PSS can match the phase separation and high-speed shear dispersion process induced by the coagulation bath, which is beneficial to maintaining continuous agglomeration and branching assembly processes. When the injection rate exceeds 1000 μL / min, the local concentration of PEDOT:PSS aqueous solution in the needle outlet and its vicinity increases too rapidly. The shear flow field is unable to disperse and stretch the newly formed aggregates in time, which can easily lead to needle blockage, excessive local aggregation, and the formation of large, non-uniform aggregates. This is not conducive to obtaining uniformly shaped nano-dendritic PEDOT:PSS aggregates.
[0011] During the coagulation bath shearing process, hydrophilic PSS tends to diffuse into the aqueous phase or coagulation bath, while hydrophobic PEDOT rapidly agglomerates, which facilitates the removal of PSS from the material. This increases the relative content and purity of PEDOT in the agglomerate. Furthermore, the non-solvent flow field of high-speed shearing induces the transformation of PEDOT from the benzoxanthine to the quinone structure. Simultaneously, the π-π stacking between quinone PEDOTs enhances their crystallinity, further improving conductivity. Meanwhile, the formed nano-dendritic structure has a high specific surface area and a three-dimensional interconnected network. The physical overlap and entanglement between the dendritic structures enhance the mechanical strength and structural stability of the material, while providing abundant conductive pathways, giving the material higher conductivity and viscosity.
[0012] The removal of PSS solves the insulation barrier problem, PEDOT crystallization solves the chain segment transport problem, and the nano-dendritic morphology solves the network connectivity problem. Together, these three factors lead to a significant improvement in conductivity and stability.
[0013] First, the dendritic structure improves the connectivity of the conductive network. Compared to isolated particles or ordinary bulk aggregates, the dendritic structure has more branches and contact points, making it easier to form continuous PEDOT conductive pathways within the membrane, thereby reducing the percolation threshold.
[0014] Second, the dendritic structure shortens the electron transport distance across the interface. In the original PEDOT:PSS film, the PEDOT-rich region may be separated by PSS, and charge carriers need to cross more insulating regions; while dendritic aggregates are more likely to overlap and interlock, forming a multi-path transport network and reducing the overall resistance.
[0015] Third, the dendritic structure helps improve the structural stability of the membrane. During film formation, the multi-branched structure can generate physical entanglement and mechanical interlocking, making the conductive network less prone to complete breakage during bending, stretching, or immersion. Therefore, it not only improves the initial conductivity but also helps maintain conductive stability.
[0016] When the solid content of PEDOT:PSS aqueous dispersion is 0.5wt%~2.0wt%, nano-dendritic PEDOT:PSS aggregates can be formed; when the solid content is below 0.5wt% or above 2.0wt%, the morphological uniformity and degree of branching of the resulting aggregates will be affected.
[0017] Preferably, the solid content of the PEDOT:PSS aqueous dispersion is 1.2 wt%.
[0018] When the solid content of the PEDOT:PSS aqueous dispersion is 1.2wt%, relatively uniform nano-dendritic PEDOT:PSS aggregates can be obtained.
[0019] Preferably, the mass ratio of PEDOT to PSS is 1:2.5.
[0020] When the mass ratio of PEDOT to PSS is 1:2.5, a relatively uniform nano-dendritic PEDOT:PSS aggregate can be obtained.
[0021] Preferably, the rotational speed of the high-speed shearing is 20,000 rpm.
[0022] Compared with 15,000 rpm and 25,000 rpm, the morphology of the nano-dendritic PEDOT:PSS aggregates obtained at a high-speed shearing speed of 20,000 rpm is more uniform.
[0023] Preferably, the coagulation bath medium is one or more of a saturated sodium chloride solution, a saturated sodium sulfate solution, a saturated sodium citrate solution, or a saturated ammonium sulfate solution.
[0024] The saturated salt solution described in this invention is preferably prepared at 25°C and reaches solid-liquid equilibrium. At 25°C, the saturated solubility of sodium chloride in water is approximately 36.0 g / 100 g water (approximately 26.5 wt% in a saturated solution); sodium sulfate is approximately 28.1 g / 100 g water (approximately 21.9 wt% in a saturated solution based on anhydrous Na₂SO₄); ammonium sulfate is approximately 76.4 g / 100 g water (approximately 43.3 wt% in a saturated solution); and trisodium citrate has a solubility of approximately 42.5 g / 100 mL water. Since sodium sulfate and trisodium citrate exist in different hydrate forms, the hydrate form of the raw materials used should be clearly defined during actual preparation, and the solid-liquid equilibrium state at 25°C, where the solution coexists with a small amount of undissolved solid, should be used as the saturation criterion.
[0025] Preferably, the injection rate of the PEDOT:PSS aqueous dispersion is 200 μL / min to 400 μL / min.
[0026] Preferably, the injection rate of the PEDOT:PSS aqueous dispersion is 300 μL / min.
[0027] When the injection rate of PEDOT:PSS aqueous dispersion is 300 μL / min, the resulting nano-dendritic PEDOT:PSS aggregates exhibit the most uniform morphology.
[0028] This invention provides a method for preparing PEDOT:PSS nanofiber structural materials.
[0029] This invention also provides the application of a PEDOT:PSS nanofiber structure material in the fabrication of DLP bioelectrodes, injectable in-situ printed conductive scaffolds, or biosensors.
[0030] Compared with the prior art, the beneficial effects of the present invention are as follows: The preparation method presented in this invention is the first to combine coagulation bath-induced phase separation with a high-speed shear flow field. PEDOT:PSS solution is uniformly injected into a high-speed rotating coagulation bath at a rate of 200 μL / min to 1000 μL / min via micro-injection. In the high-speed shear flow field, PEDOT:PSS colloid is subjected to strong stretching and shearing. Simultaneously, upon contact with the coagulation bath, salting-out-induced colloidal instability and phase separation occur. Under shear and stretching, PEDOT chain segments extend, forming a unique nano-dendritic structure. This structure significantly increases the orderliness and crystallinity of PEDOT chain segments, which is beneficial for carrier transport. XRD results show that compared with the original PEDOT:PSS, the nanodendritic aggregates exhibit a sharper diffraction peak at approximately 26° 2θ, indicating that shear force induces the ordered arrangement and increased crystallinity of PEDOT chains, resulting in an increase in conductivity of more than two orders of magnitude. In addition, during the coagulation bath shearing process, hydrophilic PSS tends to diffuse into the aqueous phase or coagulation bath, while hydrophobic PEDOT rapidly aggregates, thereby increasing the relative content and purity of PEDOT in the aggregates and further enhancing conductivity. At the same time, the formed nanodendritic structure has a high specific surface area and a three-dimensional interconnected network. The physical overlap and entanglement between the dendritic structures enhance the mechanical strength and structural stability of the material, while providing abundant conductive pathways, giving the material higher conductivity and viscosity. Furthermore, due to the removal of excess PSS, the nanodendritic PEDOT:PSS aggregates exhibit significantly reduced inherent acidity and higher biocompatibility, making them particularly suitable for applications involving direct contact with biological tissues.
[0031] The nano-dendritic PEDOT:PSS condensates prepared in this invention are highly suitable as bio-3D printing inks due to their excellent electrical conductivity, suitable rheological properties, and good biocompatibility. They can be used for precision printing of DLP bioelectrodes and also for in-situ printing of injectable bioelectrodes, showing broad application prospects in tissue engineering, neural interfaces, implantable bioelectrodes, and other fields.
[0032] The preparation method provided in this invention also achieves rapid and continuous agglomeration and molding of PEDOT:PSS. This method requires no complex spinning equipment, is simple to operate, and has high production efficiency. Attached Figure Description
[0033] Figure 1 This is a schematic diagram of the apparatus used in the method of the present invention.
[0034] Figure 2 This is a scanning electron microscope image of the nano-dendritic PEDOT:PSS condensate prepared in Example 1 of the present invention.
[0035] Figure 3This is a scanning electron microscope image of the conventional PEDOT:PSS solidified product obtained in Comparative Example 1 of this invention.
[0036] Figure 4 This is a viscosity comparison chart between Example 1 and the original PEDOT:PSS.
[0037] Figure 5 This is a comparison chart of XPS between Example 1 and the original PEDOT:PSS.
[0038] Figure 6 This is a comparison of the XRD patterns of Example 1 and the original PEDOT:PSS.
[0039] Figure 7 This is a comparison chart of the conductivity of Example 1 and the original PEDOT:PSS.
[0040] Figure 8 This is a scanning electron microscope image of the nano-dendritic PEDOT:PSS condensate prepared in Example 2 of the present invention.
[0041] Figure 9 This is a scanning electron microscope image of the nano-dendritic PEDOT:PSS condensate prepared in Example 3 of the present invention.
[0042] Figure 10 This is a scanning electron microscope image of the nano-dendritic PEDOT:PSS condensate prepared in Example 4 of the present invention.
[0043] Figure 11 This is a scanning electron microscope image of the conventional PEDOT:PSS solidified product obtained in Comparative Example 2 of this invention.
[0044] Figure 12 This is a scanning electron microscope image of the conventional PEDOT:PSS solidified product obtained in Comparative Example 3 of this invention.
[0045] Figure 13 This is a scanning electron microscope image of the conventional PEDOT:PSS solidified product obtained in Comparative Example 4 of this invention.
[0046] Figure 14 To evaluate the cytotoxicity test results of the materials using the extraction method. Detailed Implementation
[0047] The specific embodiments of the present invention are described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention. Unless otherwise specified, the experimental methods described in the embodiments of the present invention are conventional methods.
[0048] It should be noted that when numerical ranges are involved in this invention, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as in Examples 1 to 10, preferred embodiments are described in this invention to avoid redundancy. However, this invention is not limited to these, but can be specifically implemented in other ways within the scope of the technical solutions defined in the appended claims. All raw materials, reagents, instruments, and equipment used in the following embodiments of this invention can be purchased from the market or prepared by existing methods.
[0049] The following detailed description, in conjunction with embodiments of the present invention and accompanying drawings, provides a clear and complete illustration of the technical solutions in these embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0050] Example 1 A method for preparing a PEDOT:PSS nanofiber structure material includes the following steps: (1) Prepare 30 mL of saturated sodium sulfate as a coagulation bath and place the coagulation bath in a 50 mL beaker.
[0051] (2) Immerse the S18N-19G dispersing head (19mm in diameter) of the IKA T18 digital ULTRA TURRAX high-speed shear disperser below the surface of the saturated sodium sulfate solution, set the rotation speed to 20,000 rpm, start the equipment, and form a high-speed shear flow field in the saturated sodium sulfate solution.
[0052] (3) Take 10 mL of Heraeus Clevios™ PH1000 PEDOT:PSS aqueous solution (the solid content of the PEDOT:PSS aqueous solution is 1.2 wt%, and the mass ratio of PEDOT:PSS is 1:2.5) and put it into a syringe. Install the syringe on a micro-injection pump and insert the injection needle into the high-speed shear flow field near the dispersing head.
[0053] (4) Set the injection rate of the micro-injection pump to 300 μL / min, start the pump, and uniformly inject the PEDOT:PSS solution into the high-speed shear saturated sodium sulfate solution flow field, and continue injection for 30 min. During this period, the injected PEDOT:PSS solution can be seen to rapidly coagulate in the saturated sodium sulfate solution, forming a black flocculent product.
[0054] (5) Stop injection and shearing, collect the condensate in the beaker, wash it three times with deionized water to remove residual PSS and ions, and then vacuum dry it at 60℃ for 12h to obtain nano-dendritic PEDOT:PSS condensates. A schematic diagram of the apparatus used in this method is shown below. Figure 1 As shown.
[0055] Example 2 This embodiment is basically the same as Embodiment 1, except that the coagulation bath is replaced with saturated sodium chloride, while other conditions remain unchanged.
[0056] A method for preparing a PEDOT:PSS nanofiber structure material includes the following steps: (1) Prepare 30 mL of saturated sodium chloride as a coagulation bath and place the coagulation bath in a 50 mL beaker.
[0057] (2) Immerse the S18N-19G dispersing head (19mm in diameter) of the IKA T18 digital ULTRA TURRAX high-speed shear disperser below the surface of the saturated sodium chloride solution, set the rotation speed to 20,000 rpm, start the equipment, and form a high-speed shear flow field in the saturated sodium chloride solution.
[0058] (3) Take 10 mL of Heraeus Clevios™ PH1000 PEDOT:PSS aqueous solution (the solid content of the PEDOT:PSS aqueous solution is 1.2 wt%, and the mass ratio of PEDOT:PSS is 1:2.5) and put it into a syringe. Install the syringe on a micro-injection pump and insert the injection needle into the high-speed shear flow field near the dispersing head.
[0059] (4) Set the injection rate of the micro-injection pump to 300 μL / min, start the pump, and uniformly inject the PEDOT:PSS solution into the high-speed shear saturated sodium chloride solution flow field, and continue injection for 30 min. During this period, the injected PEDOT:PSS solution can be seen to rapidly coagulate in the saturated sodium chloride solution, forming a black flocculent product.
[0060] (5) Stop injection and shearing, collect the condensate in the beaker, wash it three times with deionized water to remove residual PSS and ions, and then vacuum dry it at 60℃ for 12h to obtain nano-dendritic PEDOT:PSS condensates. A schematic diagram of the apparatus used in this method is shown below. Figure 1 As shown.
[0061] The resulting product also exhibits a nanodendritic structure, but the size of the dendritic structure is slightly smaller than that in Example 1, with a dendritic diameter of 30 nm to 80 nm. Figure 8 As shown.
[0062] Example 3 This embodiment is basically the same as Embodiment 1, except that the coagulation bath is changed to a saturated sodium citrate solution, while other conditions remain unchanged.
[0063] A method for preparing a PEDOT:PSS nanofiber structure material includes the following steps: (1) Prepare 30 mL of saturated sodium citrate as a coagulation bath and place the coagulation bath in a 50 mL beaker.
[0064] (2) Immerse the S18N-19G dispersing head (19mm in diameter) of the IKA T18 digital ULTRA TURRAX high-speed shear disperser below the surface of the saturated sodium citrate liquid, set the rotation speed to 20000 rpm, start the equipment, and form a high-speed shear flow field in the saturated sodium citrate.
[0065] (3) Take 10 mL of Heraeus Clevios™ PH1000 PEDOT:PSS aqueous solution (the solid content of the PEDOT:PSS aqueous solution is 1.2 wt%, and the mass ratio of PEDOT:PSS is 1:2.5) and put it into a syringe. Install the syringe on a micro-injection pump and insert the injection needle into the high-speed shear flow field near the dispersing head.
[0066] (4) Set the injection rate of the micro-injection pump to 300 μL / min, start the pump, and inject the PEDOT:PSS solution uniformly into the high-speed shear saturated sodium citrate flow field for 30 min. During this period, the injected PEDOT:PSS solution can be seen to rapidly coagulate in the saturated sodium citrate, forming a black flocculent product.
[0067] (5) Stop injection and shearing, collect the condensate in the beaker, wash it three times with deionized water to remove residual PSS and ions, and then vacuum dry it at 60℃ for 12h to obtain nano-dendritic PEDOT:PSS condensates. A schematic diagram of the apparatus used in this method is shown below. Figure 1 As shown.
[0068] The resulting product still exhibits a nanodendritic structure, but the dendritic structure is much finer and longer, with a diameter of approximately 40 nm to 60 nm and a length of 2 μm to 5 μm, such as... Figure 9 As shown.
[0069] Example 4 This embodiment is basically the same as Embodiment 1, except that the rotation speed of the high-speed shear disperser is adjusted to 16,000 rpm.
[0070] A method for preparing a PEDOT:PSS nanofiber structure material includes the following steps: (1) Prepare 30 mL of saturated sodium sulfate as a coagulation bath and place the coagulation bath in a 50 mL beaker.
[0071] (2) Immerse the S18N-19G dispersing head (19mm in diameter) of the IKA T18 digital ULTRA TURRAX high-speed shear disperser below the surface of the saturated sodium sulfate solution, set the rotation speed to 16000 rpm, start the equipment, and form a high-speed shear flow field in the saturated sodium sulfate solution.
[0072] (3) Take 10 mL of Heraeus Clevios™ PH1000 PEDOT:PSS aqueous solution (the solid content of the PEDOT:PSS aqueous solution is 1.2 wt%, and the mass ratio of PEDOT:PSS is 1:2.5) and put it into a syringe. Install the syringe on a micro-injection pump and insert the injection needle into the high-speed shear flow field near the dispersion head.
[0073] (4) Set the injection rate of the micro-injection pump to 300 μL / min, start the pump, and uniformly inject the PEDOT:PSS solution into the high-speed shear saturated sodium sulfate solution flow field, and continue injection for 30 min. During this period, the injected PEDOT:PSS solution can be seen to rapidly coagulate in the saturated sodium sulfate solution, forming a black flocculent product.
[0074] (5) Stop injection and shearing, collect the condensate in the beaker, wash it three times with deionized water to remove residual PSS and ions, and then vacuum dry it at 60℃ for 12h to obtain nano-dendritic PEDOT:PSS condensates. A schematic diagram of the apparatus used in this method is shown below. Figure 1 As shown.
[0075] The resulting product still exhibits a nano-dendritic structure, but the degree of branching in the dendritic structure is slightly lower than in Example 1, such as... Figure 10 As shown.
[0076] Example 5 This embodiment is basically the same as Embodiment 1, except that the coagulation bath is replaced with saturated sodium chloride and saturated sodium citrate, and the solid content of the PEDOT:PSS aqueous solution is changed to 0.5wt%.
[0077] A method for preparing a PEDOT:PSS nanofiber structure material includes the following steps: (1) Prepare 30 mL of saturated sodium chloride and saturated sodium citrate as a coagulation bath, and place the coagulation bath in a 50 mL beaker.
[0078] (2) Immerse the S18N-19G dispersion head (19mm in diameter) of the IKA T18 digital ULTRA TURRAX high-speed shear disperser below the surface of the saturated sodium chloride and sodium citrate solution, set the rotation speed to 25000 rpm, start the equipment, and form a high-speed shear flow field in the saturated sodium chloride and sodium citrate solution.
[0079] (3) Take 10 mL of Heraeus Clevios™ PH1000 PEDOT:PSS aqueous solution (the solid content of the PEDOT:PSS aqueous solution is 0.5 wt%, and the mass ratio of PEDOT:PSS is 1:2.5) and put it into a syringe. Install the syringe on a micro-injection pump and insert the injection needle into the high-speed shear flow field near the dispersion head.
[0080] (4) Set the injection rate of the micro-injection pump to 300 μL / min, start the pump, and uniformly inject the PEDOT:PSS solution into the high-speed shear flow field of saturated sodium chloride and saturated sodium citrate, and continue injection for 30 min. During this period, the injected PEDOT:PSS solution can be seen to rapidly coagulate in the saturated sodium chloride and saturated sodium citrate, forming a black flocculent product.
[0081] (5) Stop injection and shearing, collect the condensate in the beaker, wash it three times with deionized water to remove residual PSS and ions, and then vacuum dry it at 60℃ for 12h to obtain nano-dendritic PEDOT:PSS condensates. A schematic diagram of the apparatus used in this method is shown below. Figure 1 As shown.
[0082] Example 6 This embodiment is basically the same as Embodiment 1, except that the coagulation bath is replaced with saturated ammonium sulfate, the rotation speed is changed to 20,000 rpm, and the solid content of the PEDOT:PSS aqueous solution is changed to 2.0wt%.
[0083] (1) Prepare 30 mL of saturated ammonium sulfate as a coagulation bath and place the coagulation bath in a 50 mL beaker.
[0084] (2) Immerse the S18N-19G dispersing head (19mm in diameter) of the IKA T18 digital ULTRA TURRAX high-speed shear disperser below the surface of the saturated ammonium sulfate solution, set the rotation speed to 20000rpm, start the equipment, and form a high-speed shear flow field in the saturated ammonium sulfate solution.
[0085] (3) Take 10 mL of Heraeus Clevios™ PH1000 PEDOT:PSS aqueous solution (the solid content of the PEDOT:PSS aqueous solution is 2.0 wt%, and the mass ratio of PEDOT:PSS is 1:2.5) and put it into a syringe. Install the syringe on a micro-injection pump and insert the injection needle into the high-speed shear flow field near the dispersing head.
[0086] (4) Set the injection rate of the micro-injection pump to 300 μL / min, start the injection pump, and uniformly inject the PEDOT:PSS solution into the high-speed shear saturated ammonium sulfate solution flow field, and continue injection for 30 min. During this period, the injected PEDOT:PSS solution can be seen to rapidly coagulate in the saturated ammonium sulfate solution, forming a black flocculent product.
[0087] (5) Stop injection and shearing, collect the condensate in the beaker, wash it three times with deionized water to remove residual PSS and ions, and then vacuum dry it at 60℃ for 12h to obtain nano-dendritic PEDOT:PSS condensates. A schematic diagram of the apparatus used in this method is shown below. Figure 1 As shown.
[0088] Example 7 This embodiment is basically the same as Embodiment 1, except that the coagulation bath is replaced with saturated sodium chloride and saturated sodium sulfate, and the rotation speed is changed to 15000 rpm.
[0089] A method for preparing a PEDOT:PSS nanofiber structure material includes the following steps: (1) Prepare 30 mL of saturated sodium chloride and saturated sodium sulfate as a coagulation bath, and place the coagulation bath in a 50 mL beaker.
[0090] (2) Immerse the S18N-19G dispersing head (19mm in diameter) of the IKA T18 digital ULTRA TURRAX high-speed shear disperser below the surface of saturated sodium chloride and saturated sodium sulfate, set the rotation speed to 15000 rpm, start the equipment, and form a high-speed shear flow field in the mixed coagulation bath.
[0091] (3) Take 10 mL of Heraeus Clevios™ PH1000 PEDOT:PSS aqueous solution (the solid content of the PEDOT:PSS aqueous solution is 1.2 wt%, and the mass ratio of PEDOT:PSS is 1:2.5) and put it into a syringe. Install the syringe on a micro-injection pump and insert the injection needle into the high-speed shear flow field near the dispersing head.
[0092] (4) Set the injection rate of the micro-injection pump to 300 μL / min, start the pump, and uniformly inject the PEDOT:PSS solution into the high-speed shear flow field of saturated sodium chloride and saturated sodium sulfate, and continue injection for 30 min. During this period, the injected PEDOT:PSS solution can be seen to rapidly coagulate in the saturated sodium chloride and saturated sodium sulfate, forming a black flocculent product.
[0093] (5) Stop injection and shearing, collect the condensate in the beaker, wash it three times with deionized water to remove residual PSS and ions, and then vacuum dry it at 60℃ for 12h to obtain nano-dendritic PEDOT:PSS condensates. A schematic diagram of the apparatus used in this method is shown below. Figure 1 As shown.
[0094] Example 8 This embodiment is basically the same as Embodiment 1, except that the injection speed of PEDOT:PSS aqueous dispersion is adjusted to 200 μL / min.
[0095] Example 9 This embodiment is basically the same as Embodiment 1, except that the injection speed of PEDOT:PSS aqueous dispersion is adjusted to 400 μL / min.
[0096] Example 10 This embodiment is basically the same as Embodiment 1, except that the injection speed of PEDOT:PSS aqueous dispersion is adjusted to 1000 μL / min.
[0097] Comparative Example 1 Compared with Example 1, Comparative Example 1 is different in that it is static solidification.
[0098] A method for preparing PEDOT:PSS material includes the following steps: Prepare a 30 mL coagulation bath of saturated sodium chloride and saturated sodium sulfate, and place the coagulation bath in a 50 mL beaker.
[0099] Take 10 mL of Heraeus Clevios™ PH1000 PEDOT:PSS aqueous solution and add it dropwise to 200 mL of saturated sodium sulfate solution using a syringe at a rate of approximately 300 μL / min, without applying any shear or stirring. During the addition, the PEDOT:PSS solution is observed to solidify in the saturated sodium sulfate solution, forming a black granular precipitate. Collect the precipitate, wash and dry it to obtain the PEDOT:PSS material.
[0100] Scanning electron microscopy revealed that the product was an irregular thin film with a relatively dense surface, and no obvious nano-dendritic structures were observed (e.g., ...). Figure 3 (As shown).
[0101] Comparative Example 2 Compared with Example 1, Comparative Example 2 differs in that it uses low-speed stirring.
[0102] A method for preparing PEDOT:PSS material includes the following steps: 200 mL of saturated sodium sulfate solution was placed in a 500 mL beaker. A magnetic stir bar was placed in the beaker, and the stirring speed was set to 500 rpm to create a low-speed stirring flow. Then, a PEDOT:PSS solution was injected into the stirred saturated sodium sulfate solution at a rate of 300 μL / min using a micro-injection pump. The product was collected and its microstructure was observed.
[0103] The results showed that the product was an irregular mixture of fibrous and sheet-like structures, occasionally containing short fiber structures, but without forming a uniform nano-dendritic network, such as... Figure 11 As shown.
[0104] Comparative Example 3 Compared with Example 1, Comparative Example 3 differs in the injection rate of the microinjection pump.
[0105] A method for preparing a PEDOT:PSS nanofiber structure material includes the following steps: (1) Prepare 30 mL of saturated sodium sulfate as a coagulation bath and place the coagulation bath in a 50 mL beaker.
[0106] (2) Immerse the S18N-19G dispersing head (19mm in diameter) of the IKA T18 digital ULTRA TURRAX high-speed shear disperser below the surface of the saturated sodium sulfate solution, set the rotation speed to 20,000 rpm, start the equipment, and form a high-speed shear flow field in the saturated sodium sulfate solution.
[0107] (3) Take 10 mL of Heraeus Clevios™ PH1000 PEDOT:PSS aqueous solution (the solid content of the PEDOT:PSS aqueous solution is 1.2 wt%, and the mass ratio of PEDOT:PSS is 1:2.5) and put it into a syringe. Install the syringe on a micro-injection pump and insert the injection needle into the high-speed shear flow field near the dispersion head.
[0108] (4) Set the injection rate of the micro-injection pump to 50 μL / min, start the pump, and uniformly inject the PEDOT:PSS solution into the high-speed shear saturated sodium sulfate solution flow field, and continue injection for 30 min. During this period, the injected PEDOT:PSS solution can be seen to rapidly coagulate in the saturated sodium sulfate solution, forming a black flocculent product.
[0109] (5) Stop the injection and shearing, collect the condensed product in the beaker, wash it three times with deionized water to remove residual PSS and ions, and then dry it under vacuum at 60°C for 12 hours to obtain the product.
[0110] The results showed that the product consisted of scattered and fragmented fibers, such as... Figure 12 As shown. This is because when the injection rate is 50 μL / min, the rate at which the PEDOT:PSS dispersion enters the sodium sulfate coagulation bath system is relatively low, making it difficult to form a stable and continuous aggregation and assembly process. In contrast, under the injection condition of 300 μL / min, the non-solvent-induced phase separation process and the high-speed shear dispersion process can be better matched, thereby obtaining PEDOT:PSS nanodendritic aggregates with more uniform morphology and more continuous branched structure.
[0111] Comparative Example 4 Compared with Example 1, Comparative Example 4 differs in the injection rate of the microinjection pump.
[0112] A method for preparing a PEDOT:PSS nanofiber structure material includes the following steps: (1) Prepare 30 mL of saturated sodium sulfate as a coagulation bath and place the coagulation bath in a 50 mL beaker.
[0113] (2) Immerse the S18N-19G dispersing head (19mm in diameter) of the IKA T18 digital ULTRA TURRAX high-speed shear disperser below the surface of the saturated sodium sulfate solution, set the rotation speed to 20,000 rpm, start the equipment, and form a high-speed shear flow field in the saturated sodium sulfate solution.
[0114] (3) Take 10 mL of Heraeus Clevios™ PH1000 PEDOT:PSS aqueous solution (the solid content of the PEDOT:PSS aqueous solution is 1.2 wt%, and the mass ratio of PEDOT:PSS is 1:2.5) and put it into a syringe. Install the syringe on a micro-injection pump and insert the injection needle into the high-speed shear flow field near the dispersion head.
[0115] (4) Set the injection rate of the micro-injection pump to 1500 μL / min, start the injection pump, and uniformly inject the PEDOT:PSS solution into the high-speed shear saturated sodium sulfate solution flow field, and continue injection for 30 min. During this period, the injected PEDOT:PSS solution can be seen to rapidly coagulate in the saturated sodium sulfate solution, forming a black flocculent product.
[0116] (5) Stop the injection and shearing, collect the condensed product in the beaker, wash it three times with deionized water to remove residual PSS and ions, and then dry it under vacuum at 60°C for 12 hours to obtain the product.
[0117] The results showed that the product was an aggregated and fused dendritic fiber, such as Figure 13 As shown. This is because when the injection rate is 1500 μL / min, the injection volume is too large, the local concentration increases too quickly, and it is easy to cause non-uniform phase separation and local aggregation. In contrast, under the injection condition of 300 μL / min, the non-solvent-induced phase separation process and the high-speed shear dispersion process can be better matched, so as to obtain PEDOT:PSS nanodendritic aggregates with more uniform morphology and more continuous branched structure.
[0118] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is the solid content of the PEDOT:PSS aqueous solution.
[0119] A method for preparing a PEDOT:PSS nanofiber structure material includes the following steps: (1) Prepare 30 mL of saturated sodium sulfate as a coagulation bath and place the coagulation bath in a 50 mL beaker.
[0120] (2) Immerse the S18N-19G dispersing head (19mm in diameter) of the IKA T18 digital ULTRA TURRAX high-speed shear disperser below the surface of the saturated sodium sulfate solution, set the rotation speed to 20,000 rpm, start the equipment, and form a high-speed shear flow field in the saturated sodium sulfate solution.
[0121] (3) Take 10 mL of Heraeus Clevios™ PH1000 PEDOT:PSS aqueous solution (the solid content of the PEDOT:PSS aqueous solution is 0.5 wt%, and the mass ratio of PEDOT:PSS is 1:2.5) and put it into a syringe. Install the syringe on a micro-injection pump and insert the injection needle into the high-speed shear flow field near the dispersion head.
[0122] (4) Set the injection rate of the micro-injection pump to 300 μL / min, start the pump, and uniformly inject the PEDOT:PSS solution into the high-speed shear saturated sodium sulfate solution flow field, and continue injection for 30 min. During this period, the injected PEDOT:PSS solution can be seen to rapidly coagulate in the saturated sodium sulfate solution, forming a black flocculent product.
[0123] (5) Stop the injection and shearing, collect the condensate in the beaker, wash it three times with deionized water to remove residual PSS and ions, and then dry it under vacuum at 60°C for 12 hours to obtain PEDOT:PSS condensate.
[0124] The product is a scattered, fragmented, and discontinuous fibrous and flocculent aggregate, without forming a uniformly interconnected nano-dendritic network.
[0125] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is the solid content of the PEDOT:PSS aqueous solution.
[0126] A method for preparing a PEDOT:PSS nanofiber structure material includes the following steps: (1) Prepare 30 mL of saturated sodium sulfate as a coagulation bath and place the coagulation bath in a 50 mL beaker.
[0127] (2) Immerse the S18N-19G dispersing head (19mm in diameter) of the IKA T18 digital ULTRA TURRAX high-speed shear disperser below the surface of the saturated sodium sulfate solution, set the rotation speed to 20,000 rpm, start the equipment, and form a high-speed shear flow field in the saturated sodium sulfate solution.
[0128] (3) Take 10 mL of Heraeus Clevios™ PH1000 PEDOT:PSS aqueous solution (the solid content of the PEDOT:PSS aqueous solution is 2.5 wt%, and the mass ratio of PEDOT:PSS is 1:2.5) and put it into a syringe. Install the syringe on a micro-injection pump and insert the injection needle into the high-speed shear flow field near the dispersing head.
[0129] (4) Set the injection rate of the micro-injection pump to 300 μL / min, start the pump, and uniformly inject the PEDOT:PSS solution into the high-speed shear saturated sodium sulfate solution flow field, and continue injection for 30 min. During this period, the injected PEDOT:PSS solution can be seen to rapidly coagulate in the saturated sodium sulfate solution, forming a black flocculent product.
[0130] (5) Stop the injection and shearing, collect the condensate in the beaker, wash it three times with deionized water to remove residual PSS and ions, and then dry it under vacuum at 60°C for 12 hours to obtain PEDOT:PSS condensate.
[0131] The product is a coarse, aggregated fibrous and blocky aggregate with poor dendritic uniformity and an indistinct open pore network.
[0132] The PEDOT:PSS nanofiber structure material can be prepared in all of the above Examples 1 to 10. The PEDOT:PSS nanofiber structure material prepared in Example 1 is preferred for performance verification.
[0133] Experimental Test (a) Structural confirmation Figure 2 This is a scanning electron microscope (SEM) image of the nano-dendritic PEDOT:PSS condensate prepared in Example 1 of this invention. Figure 2It can be seen that the product exhibits a typical nano-dendritic structure with a diameter of about 50 nm to 100 nm and a length of about 500 nm to several micrometers. The dendritic structures overlap to form a three-dimensional porous network. Figure 8 This is a scanning electron microscope (SEM) image of the nano-dendritic PEDOT:PSS condensates prepared in Example 2. Figure 8 It can be seen that a finer nano-dendritic structure is formed, with smaller branch diameters and an overall size smaller than that of Example 1. Figure 9 This is a scanning electron microscope image of the nano-dendritic PEDOT:PSS condensate prepared in Example 3. Figure 9 It can be seen that the branches are relatively slender, straight, and continuous, with a relatively large length, forming a loose open network with large pores, and the branch surface is relatively uniform. Figure 10 This is a scanning electron microscope image of the nano-dendritic PEDOT:PSS condensate prepared in Example 4. Figure 10 It can be seen that a branched structure can still be formed, but the number of branches and the connection density are lower than those in Example 1, mainly manifested as a simpler triangular or Y-shaped branching structure.
[0134] Figure 3 This is a scanning electron microscope (SEM) image of the PEDOT:PSS thin film prepared in Comparative Example 1 of this invention. Figure 3 It can be seen that the samples obtained by the direct drop method mainly exhibit a dense lamellar thin film structure, lacking obvious nano-branching and porous networks. Meanwhile... Figure 2 The PEDOT:PSS condensate prepared by the high-speed shear flow field in Example 1 presents an open and interconnected nano-dendritic network structure with abundant branches, pores and cross-linking nodes. The nano-dendritic structure is beneficial to improving the connectivity and specific surface area of the PEDOT conductive phase and constructing a continuous electron transport pathway, thereby providing a structural basis for improving the material's conductivity, composite dispersion and flexible device applications.
[0135] Figure 4 This is a comparison chart of the viscosity (rheological properties) of Example 1 and the original PEDOT:PSS. Figure 4The rheological test results show that the nano-dendritic PEDOT:PSS dispersion system exhibits significant shear-thinning characteristics. Compared with the original PEDOT:PSS, the nano-dendritic PEDOT:PSS shows higher viscosity at low shear rates, indicating that a stable physical entanglement network is formed between the dendritic aggregates. At high shear rates, its viscosity decreases rapidly, indicating that the network can undergo reversible destruction under applied shear, thereby reducing processing resistance and improving flowability. This rheological behavior gives the nano-dendritic PEDOT:PSS both good extrusion flowability and post-deposition morphology retention, providing important evidence for its potential as a printable conductive ink, flexible electrode, and patterned conductive circuit material. In contrast, the original PEDOT:PSS has lower viscosity and its viscosity does not change significantly with shear rate, making it prone to spreading and morphological instability after printing. These results indicate that the nano-dendritic PEDOT system possesses both good extrusion flowability and post-deposition morphology retention, exhibiting excellent printability and patterning potential.
[0136] Figure 5 This is a comparison chart of XPS between Example 1 and the original PEDOT:PSS. Figure 5 XPS S 2p spectroscopy results show a significant difference in the chemical state of sulfur between pristine PEDOT:PSS and nano-dendritic PEDOT:PSS. The sulfur peaks in the low binding energy region mainly belong to thiophene sulfur in the PEDOT segments, while the sulfur peaks in the high binding energy region mainly correspond to sulfonate sulfur in the PSS component. Compared with pristine PEDOT:PSS, the intensity of PSS-related sulfur peaks in nano-dendritic PEDOT:PSS is significantly reduced, indicating that high-speed shear treatment with saturated salt can effectively reduce the content or surface enrichment of insulating PSS components in the material. These results suggest that the phase separation and agglomeration process induced by the high-speed shear flow field promotes PEDOT enrichment and PSS migration / removal, thereby weakening the coating effect of PSS on the conductive segments of PEDOT, which is beneficial for constructing continuous electron transport pathways and improving the material's conductivity.
[0137] Figure 6 The XRD patterns of Example 1 and the original PEDOT:PSS are shown. The conductivity of PEDOT:PSS depends not only on the PEDOT content but also on the PEDOT segment conformation, inter-chain stacking, and conductive interconnection. The enhanced diffraction peaks of the nano-dendritic PEDOT:PSS in XRD indicate a more ordered arrangement of PEDOT segments, with inter-chain distances and transport paths more conducive to carrier migration. Combined with the reduced sulfur peak in XPS and the formation of the dendritic interconnection network in SEM, it can be concluded that high-speed shearing treatment with saturated salt is beneficial for reducing the relative PSS content, increasing the orderliness of PEDOT segments, and constructing a dendritic conductive network. These factors collectively contribute to the improvement in conductivity.
[0138] (II) Performance Study (1) Conductivity test (four-probe method) Measurement of sheet resistance Rs, film thickness t, and conductivity of nanodendritic condensate thin films Through formula Calculated.
[0139] in Figure 7 This is a comparison chart of the conductivity of Example 1 and the original PEDOT:PSS. Figure 7 It is evident that the conductivity of the nano-dendritic PEDOT:PSS film is significantly higher than that of the original PEDOT:PSS film. The original PEDOT:PSS exhibits low conductivity due to the excessive coating of insulating PSS and the relatively coiled and disordered PEDOT segments. However, after high-speed shearing treatment with saturated salt, PEDOT:PSS undergoes phase separation and agglomeration, with some PSS being removed or redistributed, resulting in increased ordered stacking of PEDOT segments and the formation of a continuously interconnected nano-dendritic conductive network. Consequently, the carrier transport resistance is significantly reduced, and the material conductivity increases to approximately 100 S / cm. This result demonstrates that the construction of a non-solvent-based high-speed shear-induced nano-dendritic structure is an important pathway to improve the conductivity of PEDOT:PSS.
[0140] (0) Biocompatibility test (CCK-8 cell viability test) Figure 14 To evaluate the cytotoxicity of the materials using the extraction method, the experiment included a blank control group, a raw PEDOT:PSS membrane extraction group, and a PEDOT:PSS dendritic aggregate membrane extraction group prepared by high-speed shearing with sodium sulfate. Each sample was extracted at 37°C for 24 h, and the resulting extracts were used to culture L929 fibroblasts. After culture, the cytotoxicity of the material extractions to L929 cells was assessed according to the standard operating procedure of the CCK-8 kit, with OD values measured at 450 nm. The cytotoxicity of the material extractions to L929 cells was evaluated by comparing the OD values and relative cell viability of different groups. Compared to raw PEDOT:PSS, the nano-dendritic PEDOT:PSS did not show significant cytotoxicity under the experimental conditions, and was comparable to the control group. Furthermore, the pH of raw PEDOT:PSS was approximately 1.5–2.5, while the pH of dendritic PEDOT:PSS was approximately 5–6.
[0141] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.
Claims
1. A method for preparing a PEDOT:PSS nanofiber structure material, characterized in that, Includes the following steps: The coagulation bath medium is subjected to high-speed shearing at a stirring speed of 15,000 rpm to 25,000 rpm to form a high-speed shear flow field. The coagulation bath medium is a saturated inorganic salt solution. PEDOT:PSS aqueous solution was injected into a high-speed shear flow field at an injection rate of 200 μL / min to 1000 μL / min for high-speed shearing. After black flocculent condensate was formed, the injection and shearing were stopped. The condensate was washed and dried to obtain nano-dendritic PEDOT:PSS condensate. The amount of PEDOT:PSS aqueous solution added shall not exceed one-tenth of the volume of the coagulation bath medium, and the solid content of PEDOT:PSS aqueous solution shall be 0.5wt%~2.0wt%.
2. The method for preparing PEDOT:PSS nanofiber structured material according to claim 1, characterized in that, The solid content of the PEDOT:PSS aqueous solution is 1.2 wt%.
3. The method for preparing PEDOT:PSS nanofiber structured material according to claim 1, characterized in that, The high-speed shearing speed is 20,000 rpm.
4. The method for preparing PEDOT:PSS nanofiber structured material according to claim 1, characterized in that, The coagulation bath medium is one or more of saturated sodium chloride, saturated sodium sulfate, saturated sodium citrate, and saturated ammonium sulfate.
5. The method for preparing PEDOT:PSS nanofiber structured material according to claim 1, characterized in that, The injection rate of PEDOT:PSS aqueous solution is 200 μL / min to 400 μL / min.
6. The method for preparing PEDOT:PSS nanofiber structured material according to claim 1, characterized in that, The injection rate of PEDOT:PSS aqueous solution is 300 μL / min.
7. The PEDOT:PSS nanofiber structure material is prepared by the method according to any one of claims 1 to 6.
8. The application of the PEDOT:PSS nanofiber structure material according to claim 7 in the fabrication of DLP bioelectrodes, injectable in-situ printed conductive scaffolds, or biosensors.